Indicators for analysis of citizens’ proposals in participatory budgeting. Towards the right to the city - Barragán Robles, Vicente (2016)
The growing importance of participatory processes as a complement to representative democracy in local spaces among other results have led to a substantial increase in the experiences of participatory budgets. These experiences have been −since its beginning− observed from different standpoints, in order to understand them and, at the same time, determine the possibilities of their primary aims. We present a methodology for the evaluation and comparison of one of the main protagonists of the processes of participatory budgets: the citizens’ proposals -equipment, work, activities, and services- in which these experiences are developed. Thereby providing quantifiable criteria for both quantitative and qualitative analysis of the objectives of participatory budgeting.